2018
DOI: 10.4018/ijhiot.2018010104
|View full text |Cite
|
Sign up to set email alerts
|

The Cyber Talent Gap and Cybersecurity Professionalizing

Abstract: Two significant issues loom throughout the cybersecurity domain. The first is the shortage of cybersecurity professionals and the second quandary is the lack of minimum entry standards in cybersecurity. Some organizations' cybersecurity operations are suffering due to the cybersecurity talent gap accompanied by the increasing sophistication and number of cyber-attack attempts. The shortage of cyber talent is rampant in private entities as in public agencies, which highlights the resolve for entry standards int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The cybersecurity talent gap is another significant issue that impacts the effectiveness of cybersecurity strategies. Nobles (2018) discusses this in "The Cyber Talent Gap and Cybersecurity Professionalizing," emphasizing the shortage of skilled cybersecurity professionals and the lack of minimum entry standards in the field. This talent gap, coupled with the increasing sophistication of cyber-attacks, highlights the need for research focused on professionalizing cybersecurity and developing national-level strategies to resolve the talent shortage.…”
Section: Identifying the Research Gap In Cybersecurity Strategiesmentioning
confidence: 99%
“…The cybersecurity talent gap is another significant issue that impacts the effectiveness of cybersecurity strategies. Nobles (2018) discusses this in "The Cyber Talent Gap and Cybersecurity Professionalizing," emphasizing the shortage of skilled cybersecurity professionals and the lack of minimum entry standards in the field. This talent gap, coupled with the increasing sophistication of cyber-attacks, highlights the need for research focused on professionalizing cybersecurity and developing national-level strategies to resolve the talent shortage.…”
Section: Identifying the Research Gap In Cybersecurity Strategiesmentioning
confidence: 99%
“…The shortage of qualified cybersecurity professionals requires that institutions of learning work to retain their cybersecurity specialists and also design programs that can be implemented to increase the number of students willing to become cybersecurity professionals and leaders in the future (Finch et al, 2020). Introducing cybersecurity courses and concepts into K-12 curricula effectively increases the number of students willing to choose a career in cybersecurity (Finch et al, 2020;Nobles, 2018). Recommended elective courses for preparing cybersecurity professionals at the high school level are not limited to Introduction to Cybersecurity, Digital Forensic Investigation Techniques, Intrusion Analysis and Response, and Introduction to Human Factors in Cybersecurity (Finch et al, 2020).…”
Section: Addressing the Scarcity Of Cybersecurity Professionalsmentioning
confidence: 99%
“…For instance, while Mountrouidou et al (2019) found that 2,300 heads of companies reported a 59% shortage of cybersecurity staff, Choudhury (2022) reported that the sustained cyberattacks and increased cybercrimes globally could be attributed to the shortage of cybersecurity professionals. In a previous study conducted by Nobles (2018), it was established that as of 2017, the global cybersecurity talent gap was two million. That is, as of 2017, the world suffered a shortage of 2 million cybersecurity professionals.…”
Section: Introductionmentioning
confidence: 99%